Lifting up the poor : a dialogue on religion, poverty & welfare reform - Bane, Mary Jo (Pew Forum dialogues on religion and public life., 2003)
People who participate in debates about the causes and cures of poverty often speak from religious conviction. But those convictions are rarely made explicit or debated on their own terms. Rarely is the influence of personal religious commitment on policy decisions examined. Two of the nation's foremost scholars and policy advocates break the mold in this lively volume, the first to be published in the new Pew Forum Dialogues on Religion and Public Life. The authors bring their faith traditions, policy experience, academic expertise, and political commitments together in this moving, pointed, and informed discussion of poverty, one of our most vexing public issues. Mary Jo Bane writes of her experiences running social service agencies, work that has been informed by "Catholic social teaching, and a Catholic sensibility that is shaped every day by prayer and worship." Policy analysis, she writes, is often "indeterminate" and "inconclusive." It requires grappling with "competing values that must bebalanced.", It demands judgment calls, and Bane's Catholic sensibility informs the calls she makes. Drawing from various Christian traditions, Lawrence Mead's essay discusses the role of nurturing Christian virtues and personal responsibility as a means of transforming a "defeatist culture" and combating poverty. Quoting Shelley, Mead describes theologians as the "unacknowledged legislators of mankind" and argues that even nonbelievers can look to the Christian tradition as "the crucible that formed the moral values of modern politics." Bane emphasizes the social justice claims of her tradition, and Mead challenges the view of many who see economic poverty as a biblical priority that deserves"preference ahead of other social concerns." But both assert that an engagement with religious traditions is indispensable to an honest and searching debate about poverty, policy choices, and the public purposes of religion.